Protein dynamics and spectroscopy for ferryl intermediate of cytochrome c oxidase: a molecular dynamics approach - Farantos, Stavros C.; Varotsis, Constantinos; Daskalakis, Vangelis; Farantos, Stavros C. (My University, 2007)
Cytochrome c oxidase is the membrane bound terminal enzyme in the respiratory chain. Molecular oxygen is reduced to water in its heme Fe/Cu B active site. The O-O bond cleavage produces the ferryl-oxo (Fe IV=O) intermediate. Molecular Dynamics calculations for a part of the protein containing over 8600 atoms are employed to probe the frequencies of vibrational modes which involve the stretching of Fe-O during protonation/deprotonation events near the active site. The role of protein frame for the spectroscopic properties of the ferryl intermediate is proved to be significant, as the intensity of the oxygen sensitive bands is controlled by conformational changes. In addition, the mechanism of the release of the produced water molecules is examined by changing the protonation state of a residue in the entrance of a proton pathway in the enzyme
Keywords: Raman spectroscopy; Proteins; Cytochrome oxidase; Molecular dynamics